Low-voltage distribution network flexible interconnection planning method considering power supply capability - LI XINYUE; ZHANG XUECHENG; CHEN YING; WEI CHEN; HAN SHUWANG; LI YANG; LUO JUNTING; MAO ZHEN; WANG LIANG; LI YONGQING; LIU JUANYU; ZHANG LAIDONG (2024)
The invention relates to a low-voltage power distribution network flexible interconnection planning method considering power supply capability. The planning method comprises the following steps: step 1, considering a low-voltage power distribution network flexible interconnection planning framework with improved power supply capability; 2, constructing a low-voltage distribution network flexible interconnection planning model considering improvement of the power supply capability; and step 3, carrying out multi-subject uncertainty refined modeling. According to the low-voltage distribution network flexible interconnection planning method considering the power supply capability, the three problems of uneven load of the distribution transformer of the low-voltage distribution network, insufficient new energy consumption capability and low voltage at the tail end of the distribution network can be effectively solved, and the power supply capability of the low-voltage distribution network is effectively improved.